Dynamic deformation of the femoral head occurs on weightbearing in Legg-Calves-Perthes disease: a translational pilot study. (10th July 2020) - Aarvold, Alexander; Lohre, Ryan; Chhina, Harpreet; Mulpuri, Kishore; Cooper, Anthony
Abstract : Aims: Though the pathogenesis of Legg-Calve-Perthes disease (LCPD) is unknown, repetitive microtrauma resulting in deformity has been postulated. The purpose of this study is to trial a novel upright MRI scanner, to determine whether any deformation occurs in femoral heads affected by LCPD with weightbearing. Methods: Children affected by LCPD were recruited for analysis. Children received both standing weightbearing and supine scans in the MROpen upright MRI scanner, for coronal T1 GFE sequences, both hips in field of view. Parameters of femoral head height, width, and lateral extrusion of affected and unaffected hips were assessed by two independent raters, repeated at a one month interval. Inter- and intraclass correlation coefficients were determined. Standing and supine measurements were compared for each femoral head. Results: Following rigorous protocol development in healthy age-matched volunteers, successful scanning was performed in 11 LCPD-affected hips in nine children, with seven unaffected hips therefore available for comparison. Five hips were in early stage (1 and 2) and six were in late stage (3 and 4). The mean age was 5.3 years. All hips in early-stage LCPD demonstrated dynamic deformity on weightbearing. Femoral head height decreased (mean 1.2 mm, 12.4% decrease), width increased (mean 2.5 mm, 7.2% increase), and lateral extrusion increased (median 2.5 mm, 23% increase) on standing weightbearing MRI compared to supine scans. Negligible deformation was observed in contra-lateral unaffected hips, with less deformation observed in late-stage hips. Inter- and intraclass reliability for all measured parameters was good to excellent. Conclusion: This pilot study has described an effective novel research investigation for children with LCPD. Femoral heads in early-stage LCPD demonstrated dynamic deformity on weightbearing not previously seen, while unaffected hips did not. Expansion of this protocol will allow further translational study into the effects of loading hips with LCPD. Cite this article: Bone Joint Open 2020;1-7:364–369.